Tacit Knowledge Sharing in Micro, Small, and Medium-Sized Enterprises: Antecedents and Its Mediators - I Made Artha Wibawa; Ni Putu Santi Suryantini; I Gusti Bagus Honor Satrya (International Journal of Social Science and Business, 2023)
Knowledge sharing as part of the source of knowledge, especially tacit knowledge, is the most transparent and subjective form of knowledge, an important driver for maintaining a competitive position and organizational sustainability. Reluctance to share knowledge is seen as unethical, which can hamper the survival of an organization. This knowledge provides human resources with qualified, superior, and long-term survival capabilities. This study aims to examine the antecedents and mediators of Tacit knowledge sharing. This research is a quantitative study with a population of 393 MSMEs in Bali Province. The sample collection method used the Solvin formula and simple random sampling to obtain 389 samples. Respondents are management, with a Likert scale questionnaire research instrument 1-5. Analysis using PLS-SEM and processed with SmartPLS 2.0 software. The results of the study show that tacit knowledge sharing has an effect on interpersonal and trust in co-workers, with the mediator variable being trusted in co-workers. This research implies communication creates effectiveness and time efficiency so as to increase trust and encourage the intention to cooperate and share knowledge secretly.